Scholars Attributed to the Emirate of Hakkari - Haidar, Mustafa Mohamed Amin; Ibrahim, Nouri Abdel Rahman (Journal of Islamic Sciences, 2019)
Kurdistan did not enjoy comfort and stability throughout the ages because of the surrounding subjective and objective circumstances. However, in the relatively short periods of comfort, prosperity, and political and economic stability, one can see the emergence of prosperous countries whose people surpassed others in all aspects of life at that time. In this study, it has been found important to investigate one such country, which is the Emirate of Hakkari. It is studied here in terms of its scholars who are dealt with following the inductive approach. The study tried to collect as many Hakkari scholars as possible and mentioned their names. It also introduced summaries of their biographies and writings, if any. It should be noted that only the cultural aspect is emphasized here because the bottom line is that it is the aspect that signifies the extent to which advancement and prosperity are achieved in other aspects of life. Certainly, if there is no political and military stability, there can be no economic, cultural, and urban prosperity, in addition to other aspects which complement the process of a decent life. During the above-mentioned short periods, science prospered and some renowned scholars appeared in those countries. They were highly versed in religion and wrote studies in their specializations. Their names and intellectual products were eventually immortal and shined brightly in historical records. One should also mention here the role played by mosques which were present in all Kurdish villages; some rare exceptions are found nowadays. Those scholars were not graduates of higher institutes and universities. On the contrary, they emerged from these mosques and their achievements made them famous. In this study, only those scholars who are attributed to the Emirate of Hakkari are investigated. This Emirate ruled for four centuries (334- 737 AH / 945- 1336 AD). During this period, renowned scholars appeared. Other scholars who appeared in the cities of this Emirate but were not recognized as Hakkari are not investigated in this study. The most important conclusions of this study are the following: • Kurdistan was an arena of conflict; conflicting forces were taking revenge on one another. Nevertheless, there were some countries which enjoyed independence; though in appearance or by name only. Those countries gave birth to renowned scholars. • Those countries were able to support the scholars who consequently became very well-known. • The Emirate of Hakkari was chosen in this study as an example. Emphasis was laid on the scholars attributed to it. Their names were mentioned as well as summaries of their biographies and writings, if any. • Paying tribute to the role played by mosques which were present in all Kurdish villages; some rare exceptions are found nowadays. This role was evident in the renowned scholars who were taught religion in these mosques and then wrote studies in their specializations. Their names and intellectual writings have become immortal and mentioned in historical records. They were not graduates of higher institutes and universities, but emerged from these mosques and so achieved a great success and exceled others.